UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS MATERI FUNGSI DAN KERAGAMAN AGAMA MENGGUNAKAN PENDEKATAN SAINTIFIK MODEL PROBLEM BASED LEARNING PADA SISWA KELAS VIII A SMP NEGERI 1 MANDASTANA KABUPATEN BATOLA - Ahdi Rizani (Universitas Lambung Mangkurat, 2015)
The purpose of this study were to: (1) Describe the activities of teachers on the implementation of the scientific approach model of Problem Based Learning on the material functions and religious diversity, (2) Describe the increased activity of the students in the material functions and religious diversity, (3) Describe the improvement of student learning outcomes in the material functions and religious diversity, and (4) Describe the response of class VIII A of SMP Negeri 1 Mandastana. This research method used classroom action research, by taking research location in class VIII A of SMP Negeri 1 Mandastana. The data analysis was qualitatively and quantitatively with persentase. The result showed that: (1) Activities of students increased in the first cycle 1 meeting with average scores of 70.6%, the second meeting of an average of 87.78%. Activities undue do students decreased from 3.2% in the first meeting becomes 2.67 in the second meeting, (2) the activity of teachers in the management of learning from the first cycle to the category quite well into both categories at the second cycle, (3) Results learn student by using model PBL can enhance students' understanding of class VIII A of SMP Negeri 1 Mandastana on the material functions and religious diversity. In the first cycle post test values obtained with an average of 71.6 We can assume that the complete classical first cycle of 75% and the second cycle an average of 83.4 to 93.8% classical completeness, and (4) the Learning IPS model Problem Based Learning the material functions and religious diversity to respond to class VIII A of SMP Negeri 1 Mandastana shown by the many students gave a positive opinion on the student questionnaire responses by 93%.Keywords: effort, improvement, activity, learning outcomes, IPS, PBL